Author's historical epics and historical memory - Toktar K. Albekov,Toktar K. Albekov, Kuralay A. Kabdeshova,Pakizat T. Auesba, Zhumashay S. Rakysh, (Opción, 2020)
The article identifies the genre specificity of the Kazakh historical epics, including the author's historical epics, which were composed orally by the author via comparative-historical and cultural-historical methods. As a result, historical epics have a special place in provoking thoughts, leading to the secrets of the soul, the psychological depth of the life phenomenon when looking through the renowned historical periods. In conclusion, the author's historical poem and historical memory are recognized as concepts that cannot be separated from each other.